The Role of the EU and NATO in the Cyprus Conflict Resolution - Nasibova, Aydan (2023)
The Cyprus conflict between the Greek Cypriot and Turkish Cypriot communities has been going on for years. The EU and NATO have played a significant role in the Cyprus conflict resolution. The EU was active in mediation efforts, including the deployment of peacekeeping forces, economic aid, and political support for a negotiated settlement. As well as NATO showed its action in security guarantees for the Republic of Cyprus and participated in joint military exercises with Turkey and Greece. Nevertheless, there are challenges that these both actors face such as the lack of progress on substantive issues and difficulties in implementing agreements. In contrast, besides those challenges, the EU and NATO interventions have had some positive effects on the conflict resolution process. They opened new avenues for dialogue and created trust-building measures.